MASTREVIRUS EFFECT ON METABOLIC AND BIOLOGICAL ACTIVITIES IN TOMATO LEAVES - S. Khalid; R. Siddique; H. Mukhtar; M. Nawaz; Hurria; Munazza (Journal of Animal and Plant Sciences, 2024)
This study was planned to illuminate the secondary metabolites of Chickpea chlorotic dwarf virus (member of mastrevirus) infected tomato plants by using phytochemical profiling procedures and their comparison with control healthy tomato plants. Metabolite profiling through GCMS indicated fourteen bioactive compounds in mastrevirus inoculated symptomatic while eight bioactive compounds were present in healthy tomato plant sample. The plant extracts were used for comparative qualitative phytochemical screening indicating the presence of alkaloid, saponins, terpenoids, tannins, phlobatannins, cardiac glycosides, anthraquinones, flavonoids and phenolic compounds in control and experimental plants. However, coumarins were absent in both samples. These metabolites were further tested for their antimicrobial potential against two gram negative bacteria viz., Pseudomonas aeruginosa and Xanthomonas campestris and two pathogenic ascomycetous fungal strains Aspergillus flavus and Penicillium verrucosum. Control and experimental plants showed maximum inhibition in methanol extract i.e., 19±0.57a against P. aeruginosa and 27±2.08a and 21±1.73ab against X. campestris respectively. Control plants exhibited maximum inhibition i.e., 30±1.53bc in chloroform extract and experimental plants showed maximum inhibition (35±3.6a) in distilled water extract against P. verrucosum. Chloroform extract of control plants and methanol extract of experimental plants showed maximum inhibitory zone (31±2.65a and 25±2.52abc) against A. flavus. Furthermore the control and experimental plants showed maximum percentage DPPH free radical scavenging activity in chloroform extract i.e., 0.25 mg/mL dilution. The findings of this current study elaborate our understanding about the metabolic changes in virus infected tomato plants.
Keywords: Tomato leaves; Chickpea chlorotic dwarf virus; Metabolite profiling; Antibacterial activity; Antifungal Activity; Antioxidant activity